Fiscal multipliers in Ireland using FIR-GEM model - Petros Varthalitis (The Economic and Social Research Institute (ESRI), 2019)
This article employs the newly developed FIR-GEM model to compute fiscal multipliers in Ireland for the main tax-spending policy instruments, namely government consumption, public investment, public wages, public transfers, consumption, capital and labour taxes. We focus on the short run fiscal multipliers as a measure to evaluate the effect of a temporary fiscal stimulus policy over three years. We find that the size of output multipliers crucially depends on the openness of the Irish economy and the method of fiscal financing employed. Our main results indicate that spending increases or tax cuts increase Irish GDP but Irish fiscal multipliers are relatively smaller in magnitude due to the openness of the economy. That is the increase in aggregate output is partly offsetdue to the negative effect of a fiscal stimulus in the Irish external balance. A fiscal expansion via spending increases or tax cuts results in a compositional change in aggregate Irish output. The positive effects on aggregate output come mostly from the stimulative effects induced in the non-tradable sector while the tradable sector remains unaffected or reduces in size. A fiscal stimulus is likely to crowd out exports and crowd in imports; this results in a deterioration in Irish trade balance. Magnitude-wise short run spending multipliers are consistently higher than short run tax multipliers. The highest fiscal multiplier effect is as a result of spending on public investment and government consumption. A fiscal stimulus via spending and consumption tax cuts have a higher effect on impact but can put upward pressures on domestic prices vis-à-vis the rest of the world and lead to a deterioration in Irish international competitiveness in the longer run. A fiscal stimulus via income tax cuts take more time to materialize and has a smaller effect on impact but the stimulus can reduce production costs and prices. This improves the international competitiveness of the Irish economy and has a more positive effect over the longer-term.
Keywords: 330